TOURIST RESOURCES AS A REGIONAL TOURISM DEVELOPMENT FACTOR (Globalization and Business, 2018)
The work refers to the opportunities of Georgia in turning into the one of the leading players of the world’s tourism market. The development of tourism in Georgia is of great importance both to the socio–economic point of view, and promotion in the world of centuries-old indigenous of Georgian nation, its history and cultural heritage. However,tourism can become a major source of replenishment of the Georgian budget and monetary resources.